Central bank dollar swap lines and overseas dollar funding costs - Linda S. Goldberg; Craig Kennedy; Jason Miu (Federal Reserve Bank of New York, 2010)
Following a scarcity of dollar funding available internationally to banks and financial institutions, in December 2007 the Federal Reserve began to establish or expand Temporary Reciprocal Currency Arrangements with fourteen foreign central banks. These central banks had the capacity to use these swap facilities to provide dollar liquidity to institutions in their jurisdictions. This paper presents the developments in the dollar swap facilities through the end of 2009. The facilities were a response to dollar funding shortages outside the United States during a period of market dysfunction. Formal research, as well as more descriptive accounts, suggests that the dollar swap lines among central banks were effective at reducing the dollar funding pressures abroad and stresses in money markets. The central bank dollar swap facilities are an important part of the toolbox for dealing with systemic liquidity disruptions.
Keywords: E44; F36; G32; 330; Banks; foreign exchange; swap; reciprocal currency arrangement; liquidity; dollar; Kapitalmangel; US-Dollar; Geldpolitik; Währungsswap; Internationale Wirtschaftsbeziehungen; Bankenliquidität; USA; Welt